1991
DOI: 10.1002/ijc.2910490322
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a new human cancer cell line secreting protease nexin‐II/amyloid β protein precursor derived from squamous‐cell carcinoma of lung

Abstract: A new cell line (LC-1/sq) of human lung squamous-cell carcinoma was established from a surgically resected specimen of primary lung cancer. Upon continuous propagation in serum-free culture medium, it secreted trypsin inhibitors into the conditioned medium. The major fraction of the trypsin inhibitor (T1-1) was purified to apparent homogeneity by anion-exchange and gel-filtration high-performance liquid chromatography (HPLC) and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) followed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In fact, we have previously purified HMTI from SFCM of the LC-l/sq cell line and confirmed it to be PN-II/APP by N-terminal amino-acid sequencing (Itoh et al, 1991). It should be noted that the 43-kDa band and the 90-to 100-kDa weak band of T-24 and CoCM-I, respectively, were also recognized FIGURE 2 -Reverse zymography for trypsin inhibitors in SFCM of human carcinoma cell lines.…”
Section: Analysis Of Sfcm Of Human Tumor-cell Linesmentioning
confidence: 77%
“…In fact, we have previously purified HMTI from SFCM of the LC-l/sq cell line and confirmed it to be PN-II/APP by N-terminal amino-acid sequencing (Itoh et al, 1991). It should be noted that the 43-kDa band and the 90-to 100-kDa weak band of T-24 and CoCM-I, respectively, were also recognized FIGURE 2 -Reverse zymography for trypsin inhibitors in SFCM of human carcinoma cell lines.…”
Section: Analysis Of Sfcm Of Human Tumor-cell Linesmentioning
confidence: 77%
“…APP also seems to function as a local mediator of growth in several malignant tumors such as lung (6), colon (20), parathyroid (21), pancreas (22), oral (23), and thyroid cancers (24). Nevertheless, the transcriptional regulation of APP has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The studies using fibroblasts revealed that APP is secreted to the cell culture medium and have an autocrine function in growth regulation (4). The secreted APP is also observed in the culture medium of tumor cells such as rat pheochromocytoma PC12 cells (5) and human lung squamous cell carcinoma cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Soluble APPα has been found to be secreted in copious amount in various human cancer cell lines [51]. It has also been linked to promoting abnormal cell growth in pancreatic cancer cells via various MAP kinase or protein kinase C signaling pathways [44], as well as in a number of solid cancers [129].…”
Section: App Proteolytic Fragmentsmentioning
confidence: 99%